All the broken girls - Bond, Linda Hurtado (Amara, imprint of Entangled Publishing, LLC, 2022)
"Crime reporter Mari Alvarez was never able to solve her mother's murder ten years ago. But when a woman is gunned down on the doorstep of her West Tampa neighborhood, Mari can't shake the eerie sense of connection. Now there have been two murders in two days. Each crime scene awash with arcane clues--and without a trace of DNA from the killer. And for each victim, a doll. The first is missing an eye. The second is missing a heart. But are these clues leading to the killer...or messages for Mari?--